A nomogram for predicting pathologic node negativity after neoadjuvant chemotherapy in breast cancer patients: a nationwide, multicenter retrospective cohort study (CSBrS-012) - Maimaitiaili, Amina; Li, Yijun; Chai, Na; Liu, Zhenzhen; Ling, Rui; Zhao, Yi; Yang, Hongjian; Liu, Yunjiang; Liu, Ke; Zhang, Jianguo; Mao, Dahua; Yu, Zhigang; et al. (Frontiers in Oncology, 2024)
We investigated the factors associated with pathologic node negativity (ypN0) in patients who received neoadjuvant chemotherapy (NAC) to develop and validate an accurate prediction nomogram.The CSBrS-012 study (2010-2020) included female primary breast cancer patients who were treated with NAC followed by breast and axillary surgery in twenty hospitals across China. In the present study, a total of 7711 eligible patients were included, comprising 6428 patients in the primary cohort from 15 hospitals and 1283 patients in the external validation cohort from 5 hospitals. Hospitals were randomly assigned. The primary cohort was randomized 3:1 and divided into a training set and an internal validation set. Univariate analysis and multivariate logistic regression analysis were performed on the training set, after which a nomogram was constructed and validated internally and externally.In total, 3560 patients (46.2%) achieved ypN0, and 1558 patients (20.3%) achieved a pathologic complete response in the breast (bpCR). A nomogram was constructed based on the clinical nodal stage before NAC (cN), ER, PR, HER2, Ki67, NAC treatment cycle, and bpCR, which are independently associated with ypN0. The area under the receiver operating characteristic curve (AUC) of the training set was 0.80. The internal and external validation demonstrated good discrimination, with AUCs of 0.79 and 0.76, respectively.We present a real-world study based on nationwide large-sample data that can be used to screen for ypN0 effectively to provide better advice for the management of residual axillary disease in breast cancer patients undergoing NAC.